Population-based birth weight reference percentiles for Chinese twins. (18th August 2017) - Dai, Li; Deng, Changfei; Li, Yanhua; Yi, Ling; Li, Xiaohong; Mu, Yi; Li, Qi; Yao, Qiang; Wang, Yanping
Abstract: Background: Birth weight percentiles by gestational age are important for assessing prenatal growth and predicting postnatal outcomes of newborns. Several countries have developed nation-specific birth weight references for twins, but China still lacks such references. Methods and results: Birth weight data for twins born between October 2006 and September 2015 were abstracted from the China National Population-based Birth Defects Surveillance System. A total of 54, 786 live twin births aged ≥28 weeks of gestation without birth defects were included in the analysis. The LMS method was adopted to generate gestational age-specific birth weight percentiles and curves for male and female twins separately. Significant differences were observed between the current reference and other references developed for Chinese or non-Chinese twins. The neonatal mortality rate in this cohort was 12.3‰, and much higher rates at very early gestation weeks were identified in small-for-gestational-age twins grouped by the newly developed reference cutoffs. Conclusions: The established birth weight centiles represent the first birth weight norm for contemporary Chinese twins and can be a useful tool to assess growth of twins in clinical and research settings. Key Messages: There have been no population-based birth weight percentiles for Chinese twins prior to this study. The established birth weight centiles for female and male twins are markedly lower than those for Chinese singletons. Twin-specific curves should be used for determining inappropriate for gestational age in twins rather than using existing singleton reference. The birth weight percentiles for twins differed significantly from those for non-Chinese twins. In addition to ethnic influences, the observed differences could be ascribed to variations in prenatal care, fetal or maternal nutrition status or other environmental factors. Neonatal mortality rates varied considerably among twins grouped by the newly developed reference percentiles. Small-for-gestational-age twins had much higher mortality than did appropriate-for-gestational-age twins, highlighting the need to reduce postnatal mortality by improving perinatal health care for twins.